Autodesk inventor 2014 and inventor LT 2014 essentials - Tremblay, Thom (John Wiley & Sons, 2013)
This full-color Autodesk Official Press guide will help you quickly learn the powerful manufacturing software's core features and functions. Thom Tremblay, an Autodesk Certified Instructor, uses concise, straightforward explanations and real-world, hands-on exercises to help you become productive with Inventor. Full-color screenshots illustrate tutorial steps, and chapters conclude with a related and more open-ended project to further reinforce the chapter's lessons.